Effect of Beam Transmission of Stable Isotopes on Online δ13C for SSAMS. Issue 5 (October 2019) - Prasad, G V Ravi; Cherkinsky, Alexander; Culp, Randy
ABSTRACT: It is known that 12 C beam transmission through the accelerator decreases at high beam currents. This effect depends on machine design and varies across different types of AMS instruments. For beam currents of about 100 μA, the effect is small on the 500 kV tandem CAMS unit, whereas beam saturation is observed for similar high beam currents on the 250 kV SSAMS unit. While this effect is very evident for high 12 C beam currents, we have also observed that even the 13 C beam is found to suffer modest transmission loss with beam current. As a result, the 13 C/ 12 C ratio does not remain constant with beam current. By correcting for the effects of 12 C beam saturation and decreased 13 C transmission, we have obtained online δ 13 C values that are more accurate and precise at moderately high beam currents for SSAMS.